2016
DOI: 10.1002/lary.25861
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and biochemical characterization of porcine tracheal cartilage

Abstract: NA. Laryngoscope, 126:E325-E331, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 55 publications
6
24
0
1
Order By: Relevance
“…This agrees with literature that found no significant difference in longitudinal versus circumferential biomechanical properties in a seeded scaffold with respect to suture retention [105]. Other studies have found out that cultured tissue to be anisotropic, showing a higher elastic moduli longitudinally [99], [106].…”
Section: Effect Of Growth Factor Supplementationsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with literature that found no significant difference in longitudinal versus circumferential biomechanical properties in a seeded scaffold with respect to suture retention [105]. Other studies have found out that cultured tissue to be anisotropic, showing a higher elastic moduli longitudinally [99], [106].…”
Section: Effect Of Growth Factor Supplementationsupporting
confidence: 92%
“…MPa) [99]. The ultimate tensile strength observed in samples with IGF-1 supplementation (1.3 MPa) were consistent with that of other scaffold-free methods (1.1…”
Section: Effect Of Growth Factor Supplementationsupporting
confidence: 87%
“…Some researchers have studied and comprehensively described the mechanical and biochemical characteristics of pig trachea, and pointed out that pig trachea is not only similar in shape to human trachea, 9 but also an excellent xenogeneic tracheal graft, which is one of the sources of tissue engineering trachea reconstruction. 10 In addition, pre-clinical studies conducted on pigs showed that there is no difference in the mechanical properties of the decellularized scaffolds before and after implantation. 11 Therefore, it is of great significance to reduce the immunogenicity of trachea while retaining the biomechanical properties for xenotracheal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the mechanical properties of the tracheal cartilage are gender and age dependent, with the tensile Young´s modulus reported in the range of 1-25 MPa [36][37][38]. Taking into consideration that the porcine trachea model was generally believed to resemble more closely that of human, the compression modulus of the porcine's trachea has been reported in the range of 1-5 MPa [39,40]. It is of note that the tensile modulus of the porous 3D-TIPS scaffolds with 50% infill density (∼1 MPa) is close to the low end of these tissue values and the decellularized rat trachea scaffolds (∼939 kPa), but much higher than collagen hydrogel (1-10 kPa) [41][42][43].…”
Section: Discussionmentioning
confidence: 99%